Anticoagulation Therapy 2016
DOI: 10.5772/64304
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombin Complex Concentrate, a General Antidote for Oral Anticoagulation

Abstract: Prothrombin complex concentrate (PCC) is used for the rapid reversal of vitamin K antagonist (VKA) anticoagulation. PCC is also applicable in situations requiring rapid reversal of anticoagulation by non-vitamin K antagonist direct thrombin and factor Xa inhibitor oral anticoagulants (NOACs), thereby making PCC a general antidote for oral anticoagulation. In this chapter, the composition of different PCC brands is reviewed and a negative effect of heparin supplement in some products is recognized. Mode of acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 120 publications
(194 reference statements)
0
13
0
Order By: Relevance
“…The thrombin generation assay is a generally accepted laboratory method to assess the reversal of DOAC anticoagulation. 5 , 29 As a first approach to study this reversal, normal plasma was treated with rivaroxaban to prolong the thrombin generation lag time to 340% (Figure 1A ) and to reduce thrombin peak (Figure 1B ) and ETP level (Figure 1C ) to 12% and 53%, respectively. In a dose‐dependent manner, the supplementation of PCC to this rivaroxaban‐treated plasma restored the ETP (Figure 1C ) and improved the thrombin peak level (Figure 1B ), whereas it hardly affected the lag time (Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thrombin generation assay is a generally accepted laboratory method to assess the reversal of DOAC anticoagulation. 5 , 29 As a first approach to study this reversal, normal plasma was treated with rivaroxaban to prolong the thrombin generation lag time to 340% (Figure 1A ) and to reduce thrombin peak (Figure 1B ) and ETP level (Figure 1C ) to 12% and 53%, respectively. In a dose‐dependent manner, the supplementation of PCC to this rivaroxaban‐treated plasma restored the ETP (Figure 1C ) and improved the thrombin peak level (Figure 1B ), whereas it hardly affected the lag time (Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“… 36 PCC dosing was based on FIX international activity units (U). 5 Relative content of the other vitamin K‐dependent coagulation factors (U/U FIX) in the used PCC batch was: FII 0.99, FVII 0.51, FX 0.86, protein S 0.16, and protein C 0.88. For FV, this was <0.01.…”
Section: Methodsmentioning
confidence: 99%
“…4F-PCC, on the other hand already contains human factors II, VII, IX, and X that increase the concentration of vitamin K dependent coagulation factors above normal generating more factor Xa and thrombin that escapes from DOAC inhibition, resulting in increased feedback amplification of the coagulation processes. 9 In a Phase I study in healthy volunteers, intravenous 4F-PCC dose-dependently reversed the effects of edoxaban 60 mg, and suggest that 4F-PCC represents a readily available option in cases where rapid reversal of edoxaban anticoagulation is essential. The double-blind, randomized, placebo-controlled, study determined the reversal effect of descending doses of 4F-PCC on bleeding duration and bleeding volume following edoxaban treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The complex of tissue factor with factor-VIIa activates the coagulation factors IX, X, (IXa, Xa) that lead to the activation of prothrombin in thrombin thus reversing factor Xa inhibition. 9 Edoxaban is the only anti-Xa inhibitor agent to have data on the effects of four-factor prothrombin complex concentrate (4F-PCC) on the reversal of bleeding. In a study of healthy subjects, the administration of a 4F-PCC at 50 IU/kg has shown to reverse the effects of edoxaban 30 mins after completing the infusion.…”
Section: Introductionmentioning
confidence: 99%
“…These coumarins act by reinstating the active vitamin K form by inhibiting vitamin K reductase [41,42]. Dosage in form of an international normalized ratio (INR) which serves as a guide remains a subject of debate and needs close monitoring [43]. However, a new class of oral, non-vitamin K anticoagulants which do not require much monitoring or dose adjustment include dabigatran, rivaroxaban, edoxaban and apixaban.…”
Section: Universal/general Antidotesmentioning
confidence: 99%